CONCEPTS AND SIGNS OF FORENSIC TACTICS (Bulletin of criminological association of Ukraine, 2023)
In this article, it has been emphasized that the question of the legal nature of forensic tactics is currently debatable, which is primarily due to the lack of unified and clear views on its concept and features. An analysis of etymological, semantic and scientific approaches to the interpretation of the terms “tactics”, “forensic tactics” has been carried out. It has been found that the essence of forensic tactics is revealed through the identification of its characteristic features. The following features of forensic tactics have been singled out and characterized: it is an independent part (section) of the science of forensics, which has close connections with its other parts - forensic techniques and methods; founded and uses within its application the assets of humanities and technical sciences; to a greater extent, it is used in connection with a conflict situation, but it also has a number of aspects of an organizational, regulatory, communicative, cognitive, etc. nature; carried out by entities authorized by the criminal procedural law (investigator, investigator, prosecutor, employees of operative units, defense lawyers, court); is a set of scientifically based techniques and recommendations, practical actions aimed at preventing and countering criminal offenses; has a dynamic subject that expands due to the need to prevent and counter new types of crime; aimed at collecting, accumulating, processing, researching and using evidentiary information to ensure the fulfillment of the tasks of criminal proceedings.
Keywords: forensic tactics; forensics; concepts; essence; signs